LIABILITY OF CORPORATION FOR EMBEZZLEMENT OF VENTURE CAPITAL FUNDS (Case Study: embezzlement of Venture Capital Funds in PT. Tata Wiratama) - Elya Kusuma Dewi (Legal Standing : Jurnal Ilmu Hukum, 2019)
This doctrinal research explained the practice of corporate crime modus. The primary data was interview result with Director General, who was share buyer, meanwhile, secondary data was company document that was related to the case, and it was analyzed qualitatively by hermeneutic interpretation techniques. Furthermore, research result showed that the impact of corporate crime law was the company must be liable in either criminal law or civil law although the managers of the company had changed.